Many Europes : - Dutton, Paul Edward (McGraw-Hill, 2014)
More and more we are challenged by today’s learning environment – students are different, digital tools are evolving, and instructors are continually asked to do more with less yet show greater results. With the creation of Many Europes, Choice & Chance in Western Civilization, an entirely integrated program, we recognize this changing environment and set out with the goal of better meeting the western civilization course challenges of improving student performance, critical analysis skills, and overall